Analysis of Heavy Equipment Quantity using Quantitative Methods Software (QM) for Windows V5 on Road Infrastructure Works - Citra, Zel; Ashadi, Reza Ferial; Wibowo, Paksi Dwiyanto; Malinda, Yosie; Apdeni, Risma; Kinasih, Reni Karno; Fitriansyah, Erlangga Rizqi (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
Data from the Geological Agency, Ministry of Energy and Mineral Resources (ESDM) in 2018, Indonesia has 37 billion tons of coal with proven reserves of 20.11 billion tons and estimated reserves of 17.02 billion tons. The total reserves increased by 12 billion tons compared to the previous year. To increase production and reserve coal, it is necessary to build mine roads to connect other mining areas. One of them is the work of transporting soil material for road embankment work. The constraints that are often encountered are limited resources and high cost of equipment. Therefore it is necessary to optimize the need for heavy equipment using Quantitative Methods Software (QM) for Windows V5. The data used in this study are primary data taken from the interview process and data in the form of related secondary documents, namely the RAB, Scheduling, SPK and other documents. The tools that will be used and optimized are a lot of digging and loading equipment such as Excavator PC400 with a bucket capacity of 2.6 m3, Excavator PC300 with a bucket capacity of 1.8 m3, Excavator with a bucket capacity of 0.8 m3 and a Dump Truck with a body capacity of 22.3 m3 as transportation equipment. The results of the research data analysis show that the most optimal number of tools needed for the road works is 1 PC300 Excavator unit, 1 PC200 unit and 3 Dump Truck (ADT) units for a work volume of 99.626 m3 and the optimal work duration is 814 hours and the labor cost is Rp. 2,781,227,681. Excavator with a bucket capacity of 0.8 m3 and a Dump Truck with a body capacity of 22.3 m3 as transportation equipment. The results of the research data analysis show that the most optimal number of tools needed for the road works is 1 PC300 Excavator unit, 1 PC200 unit and 3 Dump Truck (ADT) units for a work volume of 99.626 m3 and the optimal work duration is 814 hours and the labor cost is Rp. 2,781,227,681. Excavator with a bucket capacity of 0.8 m3 and a Dump Truck with a body capacity of 22.3 m3 as transportation equipment. The results of the research data analysis show that the most optimal number of tools needed for the road works is 1 PC300 Excavator unit, 1 PC200 unit and 3 Dump Truck (ADT) units for a work volume of 99.626 m3 and the optimal work duration is 814 hours and the labor cost is Rp. 2,781,227,681.